Motivating effort: A theoretical synthesis of the self-sufficiency and two-market theories - Yam, Kai Chi; Bumpus, Matthew F.; Hill, Laura G. (British journal of social psychology, 2012)
We conducted two experimental studies to examine the effect of introducing social and monetary incentives on participants’ (1) effort and (2) willingness to participate in a study. We found that extra credit invoked both communal sharing (CS, social reward) and market pricing (MP, monetary reward) schemas, thus leading to higher willingness to participate and greater effort in an experiment compared to an equivalent cash reward. Consistent with the potential combinational nature of different labour markets proposed by the relational theory, our results suggest that the labour market framework of monetary versus social incentive is not mutually exhaustive of all types of incentive, and the combinational effect created by introducing both labour markets may be the best motivator.